Strengthening Story Telling of the Prophet's Stories in the Qur'an for Ngaji Teachers in Surakarta - Kholilurrohman; Syafawi Ahmad Qadzafi; Aulia Normalita (LP2M of Institute for Research and Community Services - UIN Walisongo, 2025)
The low capacity of TPA teachers in Surakarta makes the implementation of effective teaching methods difficult. This study aims to improve the capacity of TPA teachers in Soloraya in strengthening effective storytelling skills. This study uses the Participatory Action Research (PAR) concept. The results of the study show that the strengthening efforts have not had a significant impact on religious teachers. Efforts to provide support in creating storybooks about the exemplary stories of the Prophets, which integrate the values of moderation, are intended to be a solution to various problems, such as low qualifications, limited human resources, and limited facilities. The development of TPQ teaching materials aims to improve the qualifications of TPA teachers in Soloraya. The implications of this study are beneficial for improving the qualifications of TPA teachers in Soloraya, so that they can teach students more efficiently.